Biochar Concrete: A state-of-the-art review - Alghawnmeh, Haneen proxy; Liu, Yue; Luo, Li; Zeng, Junjie; Zhuge, Yan (Journal of Asian Concrete Federation, 2025)
This paper reviews the studies on using biochar in concrete. An introduction to the environmental impact of cement production and the need for sustainable alternatives was first discussed, highlighting biochar's potential as a partial cement replacement. Then, the effect of biochar on cement hydration, workability, mechanical properties, durability, and microstructure was examined, with emphasis on its role in carbon sequestration. Notably, this review interrogates biochar’s contributions to compressive strength enhancement, permeability reduction, and volumetric stability via shrinkage mitigation-performance dimensions, in addition to elucidating the synergistic mechanisms between biochar and supplementary cementitious materials (e.g., fly ash, GGBS). Despite the promising results, challenges related to biochar's long-term performance and optimisation for concrete applications remain. The paper concludes by emphasising the need for further research into the durability, structural behaviour, and environmental impact of biochar-concrete composites.